PENGARUH SERVANT LEADERSHIP, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU SD NEGERI DI WILAYAH MEUREUBO KABUPATEN ACEH BARAT - Affan, Ibnu; Marwan; Siraj (LPPM-UNIKI, 2024)
This research aims to conduct an empirical study and analysis of (a) the influence of Servant Leadership on Teacher Performance, (b) the influence of Work Discipline on Teacher Performance, (c) the influence of Job Satisfaction on Performance, and (d) the influence of Servant Leadership, Work Discipline, and Job Satisfaction simultaneously on Performance. The research was conducted in 19 state elementary schools in the Meureubo area, West Aceh Regency with a sample of 170 teachers as research objects. The research was carried out descriptively associative, with analysis using the path analysis model. The research results show: (1) There is a direct and indirect influence of the Servant Leadership factor on the principal's leadership style on teacher performance by 6.28%. (2) There is a direct and indirect influence of work discipline on teacher performance, namely 10.66%. (3) There is an influence of job satisfaction of 21.32% on teacher performance. (4) Simultaneously the factors of Servant Leadership, Work Discipline and Job Satisfaction contributed to changes in teacher performance at State Elementary Schools in the Meureubo Region, West Aceh Regency by 38.2%.